Optimal tuning PID controller of unstable fractional order system by desired transient characteristics using RIM - Phu Tran Tin; Le Anh Vu; Minh Tran; Nguyen Quang Dung; Tran Thanh Trang (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, we propose the method of tuning a conventional PID controller for unstable transient characteristics. The results show that: 1) This is the novel practical method based on the desired settling time and overshoot percentage; 2) The results are close to the desired parameters; 3) The novel method can tune an unstable fractional order system by real interpolation method (RIM); 4) The novel method is simplicity and computer efficiency; 5) The novel method can find an optimal solution for tuning task in both academic and industrial purposes.